Assessing the environmental, social, and governance performance and capital structure in Europe: A board of directors’ agenda - Mohamad Ktit (21399851) (2024)
This research examines the impact of environmental, social, and governance (ESG) performance on the capital structure in European non-financial companies. The sample covers 450 non-financial organizations listed on the stock exchanges of 10 European countries (Germany, France, Luxembourg, Italy, Austria, Finland, Denmark, Portugal, the Netherlands, and Switzerland) during the period 2014–2023. This paper applies the generalized method of moments (GMM) regression to investigate the impact. The dependent variable is the leverage ratio (debt ratio) and the independent variables are ESG, environment, social, and governance factors, while controlling for firm characteristic variables (profitability, firm size, tangibility, non-debt tax shield, and market-to-book ratio) and macroeconomic variables (inflation and gross domestic product — GDP). The main finding is that ESG positively impact the leverage ratio in sustainable organizational performance. The practical implementation of this empirical research is that it helps the board of directors to make rules and regulations that help the company to report effective financial statements through clear and better information transparency and this should adjust towards the optimal capital structure. The social implication is that the organizations will increase the quality of their ESG performance which should affect the society positively. Other Information Published in: Corporate Board: Role, Duties and Composition License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.22495/cbv20i3art13